2012
DOI: 10.1021/ie202462z
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Removal by Adsorption to Fly Ash in Wastewater Generated by Mechanical Pulping

Abstract: Stringent discharge requirements call for advanced methods of wastewater treatment to take on where biological treatment fails to succeed. Here, the adsorption potential of fly ash, an on-site available and cheap material, was tested in batch and continuous flow fixed bed experiments using bleaching effluent from an integrated mill producing mechanical pulp. Various models were fitted to the experimental data to find the best description of the adsorption system and to obtain important model parameters: the Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…After settling, the supernatant was withdrawn from the beaker. Lignin residue was quantified by the UV absorbance of the sample at λ = 280 nm (Andersson et al 2012), as measured with a UV-vis spectrophotometer (HACH DR 6000). The color appearance was measured using an ADMI method (method 10048).…”
Section: Coagulation-flocculation Testmentioning
confidence: 99%
“…After settling, the supernatant was withdrawn from the beaker. Lignin residue was quantified by the UV absorbance of the sample at λ = 280 nm (Andersson et al 2012), as measured with a UV-vis spectrophotometer (HACH DR 6000). The color appearance was measured using an ADMI method (method 10048).…”
Section: Coagulation-flocculation Testmentioning
confidence: 99%
“…It was claimed that lignocelluloses and organic materials contribute to the COD of wastewater . As stated earlier, SL contained other organic materials (e.g.…”
Section: Resultsmentioning
confidence: 87%
“…Previous studies reported that the extraction of lignocelluloses from SLs would significantly reduce the chemical oxygen demand (COD) and turbidity of lignocellulosic wastewater effluents . The application of lignocelluloses extracted from SL as an energy source, fillers, flocculants, composites and resins were reported in the past.…”
Section: Introductionmentioning
confidence: 99%
“…[43] Andersson et al reported that the predominant metals in a wood fly ash consisted mainly of calcium, potassium, manganese, and magnesium. [44] In another study, fly ash from wood combustion had significantly higher sodium, potassium, calcium, magnesium, and phosphorous contents than did coal fly ash. [6] The density of FA1 and FA2 fractions are given in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary tests showed than fly ash fraction with a particle size larger than 2 mm was ineffective in adsorbing organics, and thus was excluded from this study. [44] In another study, fly ash from wood combustion had significantly higher sodium, potassium, calcium, magnesium, and phosphorous contents than did coal fly ash. [11] Table 3 lists various elements present in the biomass fly ash fractions of FA1 and FA2.…”
Section: Characterization Of Tmp Pressate and Biomass Fly Ash Samplesmentioning
confidence: 99%